Implikasi Politik Hukum Dalam Pembentukan Uu No. 13 Tahun 2003 Terhadap Perlindungan Buruh Dalam PKWT - Muhammad Bram Glasmacher (Universitas Muhammadiyah Jember, 2020)
Basically social protection is a labor protection which aims to ensure that workers / laborers are valued for their dignity and status as human beings, not only as a factor of production (external factors, but are treated as humans with all their dignity and values (internal or constitutive factors). Law in the Formation of Law No. 13 of 2003. This research study uses a research method with a normative juridical approach with data collection techniques in the form of library research.Political Politics in Lawmaking No. 13 of 2003 is influenced by the spirit of reform to better provide protection for workers / workers after the